Caesarean Section Audit: The Use of the Robson’s Criteria in a Teaching Hospital with Limited Advanced Fetal Surveillance - Olofinbiyi, Babatunde Ajayi; Awoleke, Jacob Olumuyiwa; Olaogun, Oluwole Dominic; Adefisan, Adeyemi Sunday; Olofinbiyi, Oluwafunke Rebecca; Awoleke, Adeola Olabisi; Okunola, Temitope Omoladun (International Journal of Innovative Research in Medical Science, 2020)
Background: Rising caesarean section rates have become a global health concern. The need for a contemporary objective tool for comparison of rates, optimizing and standardizing the use of caesarean section has been met by the Robson’s Ten-Group classification. However, there are no available studies auditing caesarean section rates in southern Nigeria using these criteria. Methods: All mothers delivered by caesarean section over a 12-month period at Ekiti State University Teaching Hospital, Ado – Ekiti, were prospectively captured and classified according to Robson’s 10-group classification with a view to detecting which clinically relevant groups contributed most to the caesarean section rate. Data collected were analyzed using Statistical Package for Social Sciences (SPSS) 20. Results: The total deliveries recorded over the study period was 2,139, out of which 760 underwent caesarean section, thus giving a Caesarean Section Rate of 35.5%. Group 1 had the highest contribution to Caesarean section rate, followed by Group 5. There was a statistically significant relationship between booking status of the patients and the various groups in the Robson’s classes (p < 0.001). Conclusion: There should be continuous training and drills on active management of labour, supportive companionship in labour, and improved fetal surveillance techniques to reduce the rates of primary caesarean section. Developing locally-adapted eligibility criteria to increase successful trials of labour after caesarean section, revisiting external cephalic version, and addressing potentially modifiable risks for preterm birth are advocated.